PENGARUH KEBERWUJUDAN, KEANDALAN, KETANGGAPAN, JAMINAN DAN KEPEDULIAN TERHADAP KEPUASAN DAN LOYALITAS ORANG TUA PADA MI NEGERI GROGOL - Nasirin, Irsam -; -, Mulyanto - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2013)
The purpose of this study was to examine the effect of tangible, reliability, responsiveness, assurance and care for a parent satisfaction and loyalty to the MI State Grogol Sukoharjo district. The technique of determining the sample in this study with census method that sampled all members of the population, as many as 100 parents of students, data analysis using path analysis (Path Analysis). The results of this study show a negative and significant effect tangible loyalty, reliability and no significant positive effect on loyalty, responsiveness and a significant negative effect on loyalty, security and significant positive effect on loyalty, concern has positive and significant impact on the loyalty of parents MI State Grogol Sukoharjo district. The results of path analysis is a direct path (direct effect) is the direct influence of the reliability, security, greater awareness of the influence of indirect and direct influence and responsiveness tangible smaller than the indirect effect. . Total value of determination of 0,4924 has a variance of loyalty explained by the variable reliability, security, care, and responsiveness tangible of 49,24%, the remaining 50,76% is explained variables outside the model. Variable of concern is the most dominant variable loyalty of parents in MI State Grogol Sukoharjo district. Keywords: Tangible, Reliability, Responsiveness, Assurance, Care, Loyalty.